From the soil, the foundations of Chinese society : a translation of Fei Xiaotong's Xiangtu Zhongguo, with an introduction and epilogue - Fei, Xiaotong (University of California Press, 1992)
This classic text by Fei Xiaotong, China's finest social scientist, was first published in 1947 and is Fei's chief theoretical statement about the distinctive characteristics of Chinese society. Written in Chinese from a Chinese point of view for a Chinese audience, From the Soil describes the contrasting organizational principles of Chinese and Western societies, thereby conveying the essential features of both. Fei shows how these unique features reflect and are reflected in the moral and ethical characters of people in these societies. This profound, challenging book is both succinct and accessible. In its first complete English-language edition, it is likely to have a wide impact on Western social theorists.